Eksplorasi Eksplorasi Elemen Visual Rumah Adat Citalang dalam Perancangan Motif Ready To Wear. - Khansa Anwar; Haidarsyah Dwi Albahi; Annisa Fitra (ATRAT: Jurnal Seni Rupa, 2026)
Traditional houses, as a vital component of cultural heritage, preserve conceptual historical values and identities that reflect the character of a specific locale. However, in the face of modern developments, the Citalang Traditional House encounters challenges regarding its preservation and public recognition, particularly among the younger generation. This situation necessitates creative innovations capable of revitalizing cultural values within a more relevant and applicable context. One such effort is through the design of fashion motifs that adapt visual elements from the architecture of the Citalang Traditional House into ready-to-wear fashion products. This research aims to explore the forms, structures, and philosophical meanings of the Citalang Traditional House's architecture to be interpreted into motifs that maintain cultural identity. The methodology employed is divided into four stages: pre-design, design, embodiment, and presentation. The final result consists of three ready to wear looks featuring motifs that represent the visual character and philosophical values of the Citalang Traditional House, showcased in a fashion show at the JFP (Jogja Fashion Parade) event.